Training of Luper Borubung (Surface Area of a Sphere, Cone, Cylinder) Demonstration Tools on the Surface Area of Curved Sided Template Figures (BRSL) - Tyas, Dewi Kristika Findia Ning; Kulimbang, Elieser; Asri, Harits Pratama; Langoday, Maria Novita; Dori, Novita Nanianti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Mathematics learning on the topic BRSL, particularly the determination of surface area, is often hampered by the abstract nature of the concept and the lack of adequate visual representation. This condition has the potential to hinder students' conceptual understanding and mathematical reasoning abilities. We often find that students' understanding and learning outcomes are low on this material. This luper borubung teaching aid is based on the urgency of developing learning aids that can bridge the gap between theory and visual reality. The results of the application of the luper borubung teaching aid show that 71% of students' learning outcomes are in the good category, creating a more enjoyable and meaningful learning atmosphere because they construct knowledge together in groups. The results of the attitude assessment show a percentage of cooperative attitudes, a responsible attitude , a self-confident attitude, and a meticulous attitude